HUBUNGAN JENIS MAKANAN DAN AKTIVITAS FISIK DENGAN KEJADIAN REMATIK PADA LANJUT USIA DI JORONG PADANG BINTUNGAN DI WILAYAH KERJA PUSKESMAS KOTO BARU KABUPATEN DHARMASRAYA TAHUN 2017 - Putri, Astuti Ardi (Menara Ilmu, 2018)
Rheumatic diseases is one of the chronic disease. The risk of experiencing arthritic very largein the daily invidu have an unhealthy lifestyle, such as eating the kind of food that is not good,and less physical activity. According to the World Health Organization (WHO) estimates thatapproximately 335 million people worldwide suffer from rheumatic diseases. It is estimatedthat approximately 25% of patients with rheumatoid arthritis will experience a disability as aresult of damage to the bones in the joints. The purpose of this study was to determine therelationship of food and physical activity with the incidence of arthritis in the elderly inPadang Jorong Bintungan in Region Public Health Center Koto Baru Dharmasraya 2017. Thisresearch method is survey Retrospective analytic approach using a measuring instrument viaquestionnaire. The sampling technique is random sampling with a sample of 73 respondents.Data was analyzed by univariate and bivariate statistical test using chi-square test.Results ofthis study found that the type of makanan 42 respondents (57.5%) good, 31 respondents (42.5)is not good. Physical activity 36 respondents (49.3%) good, 37 respondents (50.7%) were lessgood, 38 respondents (52.1%) had rheumatic incident, 35 respondents (47.9%) were notrheumatism ,. Results of chi-square test with a significance value of 5% (0:05), got the type offood (p-value = 0.000), physical activity (p-value = 0.000). It can be concluded there is acorrelation between the status of food and physical activity on the incidence of rheumaticlansia di Jorong Padang Bintungan In Work Area Health Center, Koto Baru Dharmasraya year2017. It is therefore expected that all parties to know any type of food that can cause arthritisand how to perform physical activity is good for the elderly.Keywords: type of food, physical activity, the incidence of arthritis